STRATEGIC MANAGEMENT ANALYSIS OF MACROECONOMIC FACTORS AFFECTING FINANCIAL PERFORMANCE IN INDIA’S VISUAL AND PERFORMING ARTS SECTOR - Janaki S; Gayathri M (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper attempts to assess the strategic management worth of the macroeconomic forces on the economic performance of firms in the Indian visual and performing arts industry on the current economic circumstances. The research is the empirical test of the key macroeconomic variables including in this case, inflation rate, interest rate, GDP growth, exchange rate fluctuation, and government expenditure on arts so as to establish their contribution towards increased increment in revenue, profitability as well as financial sustainability of arts organizations. Through the secondary data sources which includes industry reports, government publications and the finance statements of the sampled firms and institutions the research will employ the use of statistical methods such as correlation and regression analysis in identifying the significant associations amongst the macroeconomic variables and the firm performances. The conclusions indicate that cost structure and financing availability would be significantly influenced by the inflation, fluctuating interest rates, whereas the demand and financial stability would be positively influenced by the GDP growth and government assistance. The study is also able to offer effective strategic results to the arts administrators and policymakers in a rapidly shifting economic framework so as to augment the strength, best economic planning, and reactive plans.